1978
DOI: 10.1126/science.628835
|View full text |Cite
|
Sign up to set email alerts
|

Pyrazole-Induced Thyroid Necrosis: A Distinct Organ Lesion

Abstract: One oral dose of pyrazole caused necrosis of rat thyroid follicular epithelial cells but spared the parafollicular (C) cells and the parathyroid glands. Serum thyroxine (T4) and triiodothyronine (T3) were significantly decreased on day 3 after pyrazole administration and were immeasurable on day 5. At day 5 the thyroid was enlarged and the concentration of thyroid-stimulating hormone in the serum was increased, indicating an appropriate pituitary response to a primary lesion in the thyroid. Doses of pyrazole w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…In the zebrafish eleutheroembryo model, exposure to BPA at MTC did not modify the IT4C, so it was not classified as a TGFD. Pyrazole has been reported to induce necrosis in rat thyroid follicular cells and a significant decrease of about 80% in IT4C was observed in zebrafish eleutheroembryos using TIQDT. Finally, BP3 and linuron had no effect in thyroid-relevant in vitro assays and no thyroid disrupting effects have been reported in mammalian models.…”
Section: Discussionmentioning
confidence: 99%
“…In the zebrafish eleutheroembryo model, exposure to BPA at MTC did not modify the IT4C, so it was not classified as a TGFD. Pyrazole has been reported to induce necrosis in rat thyroid follicular cells and a significant decrease of about 80% in IT4C was observed in zebrafish eleutheroembryos using TIQDT. Finally, BP3 and linuron had no effect in thyroid-relevant in vitro assays and no thyroid disrupting effects have been reported in mammalian models.…”
Section: Discussionmentioning
confidence: 99%
“…Electron microscopy revealed that the lesions progressed from dilation of the endoplasmic reticulum of the follicular epithelial cells, to vesiculation, mitochondrial damage, clumping of chromatin along nuclear membranes and final necrosis and desquamation of the cells [6]. This effect of pyrazole on thyroid tissue did not occur in the trout [21].…”
Section: Preclinical Toxicologymentioning
confidence: 83%
“…In this species, pyrazole (1400 mg/kg) results in a 90-100% incidence of thyroid lesions [6]. In contrast to the rat, pyrazole did not cause a block of thyroid function in rainbow trout, where it was shown to only depress plasma T 3 [21].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 2 more Smart Citations